Public Debt Frontier: a Python Toolkit for Analyzing Public Debt Sustainability - Fernández-de-Córdoba-Martos, Gonzalo; Molinari, Benedetto; Torres-Chacón, José Luis (MDPI, 2021)
This study proposes a synthetic visual indicator with which to perform debt sustainability analysis using dynamic general equilibrium models. In a single diagram, we summarized the general equilibrium relationships among economic activity, government budget, and the maximum amount of sustainable public debt. Then, we measured sustainability using the distance of actual debt from the model-consistent maximum debt. This indicator can be implemented with any DSGE model; as a backing theory, we used a neoclassical model augmented with endogenous tax revenues, disaggregated public spending, different production technologies for public and private goods, non-atomistic wage setters in public labor (unions), and a fully specified maturity curve for public bonds. We provided an example of its usage using the case of Greece during the last public debt crisis. To perform the numerical analysis, we developed original software, whose advantage is allowing an audience without expertise in DSGE models to perform general equilibrium debt sustainability analyses without requiring an understanding of the technicalities of DSGE models.
Keywords: Python (Lenguaje de programación); Deuda pública; Debt Sustainability Analysis; Fiscal policy; Debt-dependent government spending; DSGE model; Python; Toolkit